Stroke radiology and distinguishing characteristics of intracranial atherosclerotic disease in native South Asian Pakistanis. (27th September 2012) - Khan, Maria; Rasheed, Asif; Hashmi, Saman; Zaidi, Moazzam; Murtaza, Muhammad; Akhtar, Saba; Bansari, Lajpat; Shah, Nabi; Samuel, Maria; Raza, Sadaf; Khan, Umer Rais; Ahmed, Bilal; et al.
Abstract : Background: There are no descriptions of stroke mechanisms from intracranial atherosclerotic disease in native South Asian Pakistanis. Methods: Men and women aged ≥18 years with acute stroke presenting to four tertiary care hospitals in Karachi, Pakistan were screened using magnetic resonance angiography/transcranial Doppler scans. Trial of ORG 10172 in Acute Stroke Treatment criteria were applied to identify strokes from intracranial atherosclerotic disease. Results: We studied 245 patients with acute stroke due to intracranial atherosclerotic disease. Two hundred thirty scans were reviewed. Also, 206/230 (89·0%) showed acute ischaemia. The most frequent presentation was with cortically based strokes in 42·2% (87/206) followed by border‐zone infarcts (52/206, 25·2%). Increasing degrees of stenosis correlated with the development of both cortical and border‐zone strokes ( P = 0·002). Important associated findings were frequent atrophy (166/230, 72·2%), silent brain infarcts (66/230, 28%) and a marked lack of severe leukoaraiosis identified in only 68/230 (29·6%). A total of 1870 arteries were studied individually. Middle cerebral artery was the symptomatic stroke vessel in half, presenting with complete occlusion in 66%. Evidence of biological disease, symptomatic or asymptomatic was identified in 753 (40·2%) vessels of which 543 (72%) were significantly (>50%) stenosed at presentation. Conclusion: Intracranial atherosclerotic disease is a diffuse process in Pakistani south Asians, with involvement of multiple vessels in addition to the symptomatic vessel. The middle cerebral artery is the most frequent symptomatic vessel presenting with cortical embolic infarcts. There is a relative lack of leukoaraiosis. Concomitant atrophy, silent brain infarcts and recent ischaemia in the symptomatic territory are all frequently associated findings.